Languages and Linguistic Issues before the International Criminal Court - Kovács Péter (HUNGARIAN YEARBOOK OF INTERNATIONAL LAW AND EUROPEAN LAW, 2019)
The present article deals with some of the language issues present before the International Criminal Court (ICC). These issues do not simply result fromthe challenges of translation to/fromEnglish and French but also fromthe fact that the English and French used before the ICC are specialist legal languages with centuries-old practice behind their well-established notions (e.g. ‘no case to answer’). There are numerous other languages used by witnesses and victims with various backgrounds in the different cases and situations. They are mostly local, sometimes tribal languages often lacking the vocabulary necessary to describe complex legal issues, to deal with notions and phenomena ofmodern substantive or procedural law. It is equally important to note that there are always special local notions, which are impossible to translate with a single term, sometimes becoming a part of the English or French language of the procedure. Other languages, however, may bring with them their own special legal or historical-legal vocabulary, which must be reflected on in order to unpack its proper meaning. As such, language issues are omnipresent before the ICC, having also an impact on the budget of the Court. The efficient and accurate work of interpreters and translators is of outmost importance fromthe point of view of fair trial, rights of the accused but also from the perspective of access to information for victims, witnesses or local communities who are following the judicial procedure from home.